Effect of acid-ethanol treatment followed by ball milling on structural and physicochemical characteristics of cassava starch - Cavallini, Carolina M. [UNESP] (2010)
Structural and physicochemical characteristics of cassava starch treated with 0.36% HCl in anhydrous ethanol during 1 and 12 h at 30, 40, and 50 degrees C followed by ball milling for 1 h were analyzed. Average yield of acid-ethanol starches reached 98% independent of the treatment conditions. Solubility of acid-ethanol starches increased with reaction temperature and time, but it did not change after ball milling. Granule average size reduced with chemical treatment from 25.2 to 20.0 mu m after 12 h at 50 degrees C. Ball milling decreased the granule average diameter of the native starch and those chemically treated at 30 degrees C/1 h or 40 degrees C/1 h, but it did not alter the starches treated for 12 h, independent of temperature. From scanning electron microscopy (SEM), starch granules presented round shape and after modification at 50 degrees C/12 h, before and after ball milling, showed a rough and exfoliated surface. Some granules were deformed, suggesting partial gelatinization that was more intense after milling. Starch crystallinity increased as temperature and time of chemical treatment were increased, while amylose content, intrinsic, and pasting viscosities decreased. Gelatinization temperatures increased for all chemical starches. The findings can be related to the preferential destruction of amorphous areas in the granules, which are composed of amylose and amylopectin. After ball milling, the starch crystallinity decreased, amylose content, intrinsic, and pasting viscosities kept unchanged and gelatinization temperatures and enthalpy reduced. Ball milling on native and chemical starches caused the increase of amorphous areas with consequent weakening and decreasing of crystalline areas by breaking of hydrogen bonds within the granules.